Human herpesvirus 6 lymphadenitis in drug rash with eosinophilia and systemic symptoms syndrome: a lymphoma mimic. Issue 7 (10th March 2017) - Johnson, Steven; Mathews, Stephanie; Hudnall, S. David
Abstract : Aims: Lymphadenopathy, haematological abnormalities and constitutional symptoms are among the non‐specific manifestations seen in drug rash with eosinophilia and systemic symptoms (DRESS), an uncommon but potentially fatal cutaneous adverse drug reaction. The ubiquitous human herpesvirus 6 (HHV‐6) plays a unique role in the pathogenesis of DRESS, with emerging data suggesting that reactivation occurs in most cases and contributes to the clinical manifestations, including lymphadenopathy. Further, in the appropriate clinical context, demonstration of HHV‐6 reactivation may lend support to a diagnosis of DRESS. The histopathology of DRESS‐associated HHV‐6 lymphadenitis is reported rarely, with morphologic and immunophenotypic characteristics concerning for T cell lymphoma. The aim is to characterize the histopathology of HHV‐6 lymphadenitis in the context of DRESS and to highlight this as an important cause of lymphadenopathy that may be a clinical, morphologic and immunophenotypic mimic of lymphoma. Methods and results: We describe a case of lymphoma‐mimicking lymphadenitis in which the histopathological demonstration of reactivation of HHV‐6 infection lent support to the clinical diagnosis of DRESS. Conclusion: Lymph node biopsies concerning for T cell lymphoma should be evaluated for HHV‐6 involvement in a clinical context suggestive of DRESS.